Size Determination in Chemically Grown PbS Nano Particles Using Different Theoretical Approach. Issue 1 (23rd February 2023) - Kumar, Vinay; Kumar, Pranav; Bhattacharya, B.; Alheety, Mustafa A.; Zakariya'u, Ibrahim; Kumar, Pawan
Abstract: Chemical bath method is adopted for growth of lead sulfide nano particles in methanolic solution of Pb(No3 )2 . Sulfur exchange is achieved by the controlled reaction of Na2 S. The optical absorption studies have been done for obtained colloidal solution. The prepared particles are characterized by UV/Visible absorption spectra in the range 700–250 nm and the corresponding energy band gaps have been calculated assuming the effective masses of the electrons and holes in the nano particles to be same as that of bulk. The particle size has been determined by using the Wang Mahler and Brus L.E. Theoretical approaches. It is found that without using any capping agent the band gap of the compound gradually increases as the size of the particle decreases.